A dual-mode optical assay of Hg (Ⅱ) ions via simulated oxidase and fluorescence based on composites formed by crosslinking of glutaraldehyde and chitosan-nano-selenium. (August 2022) - Lu, Changfang; Wang, Yutong; Zhang, Wei; Zhang, Yu; Chen, Yinyin; Xiang, Gang; Wang, Xianxiang
Abstract: The crosslinking of glutaraldehyde (GA) and nano-selenium coated chitosan (CS-SeNPs) afforded composites (GA–CS–SeNPs) which exhibit new properties. In addition to having mimic enzyme activity of CS-SeNPs, these composites exhibit fluorescence, which CS-SeNPs did not possess. The GA–CS–SeNPs can catalyze the chromogenic process of oxidation of substrate TMB at 20 °C and pH of 3.5, and under the excitation wavelength of 440 nm, the composites can emit strong fluorescence. The presence of mercury (II) (Hg 2+ ) inhibited the color process of catalytic oxidation of 3, 3, 5, 5, -tetramethylbenzidine (TMB) and enhanced the fluorescence intensity of the composites to some extent. Therefore, using the fluorescence and mimicking enzyme properties of GA–CS–SeNPs, a fluorescent and colorimetric (dual-mode) determination of Hg 2+ was developed with good selectivity and high sensitivity. The linear determination ranges of Hg 2+ were 0–55 μM and 0–50 μM for fluorescent and colorimetric assays, respectively, and the limits of detection (LOD) for the dual-mode assay were as low as 0.34 μM and 0.40 μM, respectively. In addition, this new method was successfully implemented for dual-mode determination of Hg 2+ in real samples. Graphical abstract: A fluorescent turn-on and colorimetric (dual-mode) determination of Hg 2+ was developed based on composites formed by crosslinking of glutaraldehyde and chitosan-nano-selenium. Image 1 Highlights: The crosslinking of GA improved the properties of selenium nanomaterials. The obtained composites GA–CS–SeNPs had oxidase-like activity and strong fluorescence emission. A new dual-mode (colorimetric and fluorometric) determination of mercury (II) was established.